Analisis Pengaruh Variasi Kontaminasi Air Laut Terhadap Perubahan pH dan Sifat Reologi Lumpur Pemboran pada Sumur IM Lapangan ME - Indah Mentari Ephiphania; Mirza Mirza; Esterina Natalia Paindan; Baiq Maulinda Ulfah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Drilling mud plays an important role in oil and gas drilling operations as it functions to transport cuttings, maintain wellbore stability, and control formation pressure. The performance of drilling mud may deteriorate due to contamination, one of which is seawater contamination that can affect the pH value and rheological properties of the drilling mud. This study aims to analyze the effect of seawater contamination on the pH and rheological properties of drilling mud used in Well "IM" of the "ME" Field. This research employed a quantitative method with an experimental approach conducted at the Drilling Laboratory of Sekolah Tinggi Teknologi Migas Balikpapan using seawater contamination levels of 1%, 3%, 5%, 7%, and 9%. The parameters evaluated were pH, Plastic Viscosity (PV), Yield Point (YP), and Gel Strength at 10 seconds and 10 minutes. The results showed that increasing seawater contamination reduced the quality of the drilling mud. The pH value decreased from 8.61 to 5.80, while Plastic Viscosity (PV) decreased from 12 cP to 6 cP, Yield Point (YP) from 31 lb/100 ft² to 21 lb/100 ft², Gel Strength at 10 seconds from 13 lb/100 ft² to 8 lb/100 ft², and Gel Strength at 10 minutes from 15 lb/100 ft² to 10 lb/100 ft².